PERANCANGAN ALAT TROLI ERGONOMIS UNTUK PENERAAN POMPA UKUR BAHAN BAKAR MINYAK DI SPBU - Kobat, Michael An Nahl; Widodo, Lamto; Sukania, I Wayan (Jurnal Mitra Teknik Industri, 2024)
Fuel Oil Meter (BBM), hereinafter referred to as Flow Meter, is a dynamic fluid measuring instrument for fuel oil which consists of a measuring body and a calculating body to measure the volume of liquid flowing through the measuring body. The research was carried out by conducting a survey and qualitatively, namely distributing questionnaires. In this study the population was 10 people. Interviews and filling out the Nordic Body Map questionnaire were distributed to ten workers who were carrying out tests at Public Fuel Filling Stations (SPBU). It is known that the greatest extent is directed at the sole of the left foot and pain in the sole of the right foot. After measuring and analyzing body posture in each working position, REBA calculations are then carried out for each working position. At the trolley design stage, the development of ergonomic trolley innovations is analyzed using the SWOT method to determine weaknesses, opportunities and dangers. In developing an idea, a technique is needed to solve problems creatively, namely by using SCAMPER. By using SCAMPER and SWOT, a product has been created that meets the desires of consumers, namely by adding adequate features and in accordance with the needs of workers to cover worker complaints, including a water level feature that is embedded in the surface base for placing vessels to make it easier for workers to level the terrain. which is assisted by a bottle jack which can affect the results of the test. This ergonomic trolley has a length of 125cm and a width of 85cm, a vessel base with a diameter of 60cm and 3 bottle jacks embedded in the surface of the trolley.